Cross-border online shopping experiences of Chinese shoppers. Issue 2 (3rd October 2019) - Baek, Eunsoo; Lee, Ha Kyung; Choo, Ho Jung
Abstract : Purpose: The purpose of this paper is to investigate how geographic cues embedded in a website affect Chinese consumers' cross-border shopping experiences. The study simultaneously explores the effect of telepresence on shoppers' perceptions of product authenticity and their trust in retailers, key drivers of behavioral intentions. Design/methodology/approach: Two experimental conditions were utilized. Geographic cues depicted a famous shopping district in the retailer's country (South Korea) or the shopper's country (China). Study participants were female Chinese consumers in their 20s and 30s who had purchased Korean fashion products in the past ( n =236). Structural equation modeling was conducted using AMOS 21.0. Findings: Results indicate that participants in the "retailer's country" experimental condition experienced higher telepresence and greater perceptions of product authenticity. Furthermore, telepresence increased participants' trust in the retailer and perceived product authenticity, which led to positive behavioral intentions. Practical implications: Findings offer important implications for cross-border online retailing. First, results suggest a highly successful tactic for enhancing shoppers' perceptions of product authenticity and retailer trust on a cross-border platform. Second, cross-border online business professionals should focus on the role of telepresence. Finally, this study provides insight about Chinese cross-border shoppers. Originality/value: This study contributes to the literature on cross-border online shopping. It suggests that the strategic use of geographic cues on a website can provide an experiential benefit, telepresence, to cross-border shoppers. The study's findings provide a novel insight into possible unique success factors in cross-border e-commerce.